DESENVOLVIMENTO ÓSSEO DE FRANGOS DE CORTE CRIADOS EM DIFERENTES DENSIDADES DE CRIAÇÃO - SOUZA, Jéssica Andrade Diniz; OLIVEIRA, Andréia Fróes Galuci; HENRIQUE, Cleoneide dos santos; MELLO, Bruna Finotti Fonseca Reis; FERREIRA, Thales silva; STEINER, Fábio (ANAIS DO ENIC, 2017)
-